2019
DOI: 10.1590/1981-52712015v43n4rb20190078
|View full text |Cite
|
Sign up to set email alerts
|

Egressos de um Mestrado Profissional em Saúde da Família: Expectativas, Motivações e Contribuições

Abstract: RESUMO O modelo de assistência à saúde pautado na Estratégia Saúde da Família, criada no início da década de 1990, incentivou mudanças no ensino na saúde, evidenciando a necessidade de criar cursos de pós-graduação lato e stricto sensu voltados para capacitar profissionais que fomentem a atenção integral à saúde. Avaliações periódicas são realizadas e estimuladas pela Capes/MEC a fim de manter a qualidade dos cursos de pós-graduação, mas ainda são escassas as avaliações de cursos de mestrado profissional em sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
4
0
3
Order By: Relevance
“…This article describes the UNA-SUS network's specialization courses in family health that were offered to physicians, dental surgeons and nurses from primary health care and reached 61.635 enrollments between 2013 and 2017. The respondent pro le is in line with other educational offerings from the UNA-SUS network, in which most students are female, white, Brazilian, and aged 40 years or less [4,12,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article describes the UNA-SUS network's specialization courses in family health that were offered to physicians, dental surgeons and nurses from primary health care and reached 61.635 enrollments between 2013 and 2017. The respondent pro le is in line with other educational offerings from the UNA-SUS network, in which most students are female, white, Brazilian, and aged 40 years or less [4,12,17].…”
Section: Discussionmentioning
confidence: 99%
“…In general, the graduate course in family health has been considered satisfactory by participants in Brazil. A study conducted in Rio de Janeiro that surveyed 102 graduates of a professional master's course in family health via an online questionnaire in 2014 found that 77% of respondents considered this educational process to have made a positive contribution to their professional practice [12]. This nding is corroborated by an online survey conducted in northeastern Brazil with 225 graduates of a master's program in family health, in which most students assigned high scores to the skills they acquired, emphasizing that graduate studies contributed to their professional activity from the perspective of integrated health care [13].…”
Section: Discussionmentioning
confidence: 99%
“…Como ressaltam Viniegra et al (2019), "A análise de egressos realizada pela instituição de ensino contribui com informações sobre o impacto do curso na vida do aluno e na sociedade, identificando dificuldades e êxitos". Por meio dos dados coletados e da satisfação de cada egresso com a pós-graduação, pode-se averiguar de quais formas o presente Mestrado…”
Section: Discussionunclassified
“…The available research on graduate students is recent and concentrated in specific fields of knowledge, such as Health (Ferreira et al, 2015;Morrayre, 2013;Louzada;Silva Filho, 2005;Mendes;Venceslau;Aires;Prado Júnior, 2010;Teixeira et al, 2017;Viniegra et al, 2019); Sciences, Technology, Engineering, and Mathematics (STEM) (Crede, 2011;Head et al, 2021;Maclachlan, 2006;Mendes, 2017;Velho, 2012); Education (Abramowicz et al, 2009); Law (Marks;Moss, 2016); and Administration (Mccray;Joseph-Richard, 2021;Meurer;Costa, 2020;Tenorio, 2020;Stewart Williamson;King Junior, 2017). One can list at least three predominant themes in these studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first addresses the factors that influence the completion of the course, such as guidance (Bryson;Kowalske, 2022;Costa, Sousa;Silva, 2014;Denis;Colet;Lison, 2019;Duke;Denicolo, 2017;Ismail;Majid;Ismail, 2013;Leite Filho;Martins, 2006;Pyhältö, Vekkaila;Keskinen, 2015), the sociodemographic characteristics of students (parental education, race/skin-color/ethnicity, gender, nationality) (Posselt;Grodsky, 2017), and the integration of students into the course (Castelló et al, 2017;Devos et al, 2017;Hay;Samra-Fredericks, 2016). The second theme brings together studies that analyze the profile of students who graduated with subsequent professional development (Louzada;Silva Filho, 2005;Mendes;Venceslau;Aires;Prado Júnior, 2010;Tenorio, 2020;Viniegra et al, 2019). Finally, there are several studies on the quality of life and mental health of graduate students (Imeri et al, 2021;Levecque et al, 2017;Malagris et al, 2009;Mccray;Joseph-Richard, 2021;Teixeira et al, 2017;Radons, Cunha;Lucca, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%